2022
DOI: 10.3390/jcm11133788
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Apixaban in over 3.9 Million People with Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Background: There is a plethora of real-world data on the safety and effectiveness of direct-acting oral anticoagulants (DOACs); however, study heterogeneity has contributed to inconsistent findings. We compared the effectiveness and safety of apixaban with those of other direct-acting oral anticoagulants (DOACs) and vitamin K antagonists (VKA e.g., warfarin). Methods: A systematic review and meta-analysis was conducted retrieving data from PubMed, SCOPUS and Web of Science from January 2009 to December 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 86 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…Neither network nor traditional meta-analysis indicated that DOACs were ineffective in reducing intracranial hemorrhage. Consistent with the present study (Buckley et al, 2022), the use of DOACs did not yield beneficial outcomes in terms of reducing bleeding rates among ESRD patients with AF undergoing dialysis. Among patients receiving dialysis and diagnosed with AF, treatment with DOACs was associated with a 28% increased risk of bleeding events.…”
Section: Discussionsupporting
confidence: 87%
“…Neither network nor traditional meta-analysis indicated that DOACs were ineffective in reducing intracranial hemorrhage. Consistent with the present study (Buckley et al, 2022), the use of DOACs did not yield beneficial outcomes in terms of reducing bleeding rates among ESRD patients with AF undergoing dialysis. Among patients receiving dialysis and diagnosed with AF, treatment with DOACs was associated with a 28% increased risk of bleeding events.…”
Section: Discussionsupporting
confidence: 87%
“…Results concur with several studies showing lower gastrointestinal and nonintracranial bleeding rates for apixaban compared with other DOACs. 2,10,11 Findings were consistent across a suite of thoughtfully selected sensitivity and subgroup analyses and were robust when using an intention-to-treat rather than an on-treatment exposure definition. Characterizing major bleeding as hospitalization for any bleeding is a sensitive definition that reduces misclassification Stroke.…”
Section: See Related Article P 1161mentioning
confidence: 54%
“…While our center can receive same day results for apixaban levels, we do realize that is not an option at all institutions. The described prophylactic and therapeutic apixaban levels have been demonstrated to have appropriate efficacy, safety, and low events rates in an analysis 219 pediatric patients, along with five HM3 VAD patients, from our institution, 17,18 along with a large meta‐analysis in adults 19 . It has been demonstrated that chromogenic anti‐factor Xa assay calibrated with heparin standards shows a correlation between apixaban levels and LMWH levels 20 .…”
Section: Discussionmentioning
confidence: 88%
“…The described prophylactic and therapeutic apixaban levels have been demonstrated to have appropriate efficacy, safety, and low events rates in an analysis 219 pediatric patients, along with five HM3 VAD patients, from our institution, 17,18 along with a large meta-analysis in adults. 19 It has been demonstrated that chromogenic anti-factor Xa assay calibrated with heparin standards shows a correlation between apixaban levels and LMWH levels. 20 These previously described findings correlate with our experience as well, with a goal LMWH of greater than 1.5 units/mL suggesting appropriate apixaban anticoagulation.…”
Section: Discussionmentioning
confidence: 99%